Estudo de viabilidade de catálise enzimática por lipases para a hidrólise e síntese de intermediário da indústria de antibióticos - Costa, Ana Paula Lima da (2024)
Antibiotics are considered one of the most successful discoveries in the history of medicine. However, the production of these drugs via chemical route generates harmful effluents. Being an intermediate for the enzymatic synthesis of important β-lactam antibiotics, D-phenylglycine methyl ester (PGME) is produced using highly toxic reagents, with low product enantioselectivity. Enzymatic processes have emerged as a promising and sustainable alternative for the synthesis of antibiotics and their intermediates, and lipases stand out for catalyzing a variety of reactions. Thus, this work aimed to develop an unprecedented enzymatic route for the synthesis of PMGE from the esterification reaction of the amino acid D-phenylglycine (Phenylglycine-PG) with methanol catalyzed by commercial lipases. The initial study evaluated solvents favorable to PG solubility, however it proved to be poorly soluble in the solvents tested, requiring the addition of 0.5 M hydrochloric acid or ionic liquid to observe any solubility. The specificity of a range of lipases in relation to the hydrolysis activity of PGME was investigated, in order to verify that the lipases evaluated showed good performance in hydrolysis, with the potential to catalyze the reverse reaction (esterification), with emphasis on lipase B from Candida antarctica which yielded higher reaction rate and better substrate affinity based on Michaelis-Menten kinetic parameters. A new gas chromatography method was implemented to separate and characterize PGME, whose strategy is little explored in the literature. Different esterification reaction tests were carried out and only with the aid of the liquid chromatography technique coupled to a mass spectrometer (LC/MS) it was possible to prove the synthesis of the ester, which showed low conversions, even so, showing itself to be unprecedented in the literature. There is limited information about the reaction via the enzymatic route o produce PGME, therefore, the study developed could contribute to the advancement of knowledge in this area.